2022
DOI: 10.1038/s41598-022-20236-1
|View full text |Cite|
|
Sign up to set email alerts
|

Novel D-form of hybrid peptide (D-AP19) rapidly kills Acinetobacter baumannii while tolerating proteolytic enzymes

Abstract: Antimicrobial peptides (AMPs) are being developed as potent alternative treatments to conventional antibiotics which are unlikely to induce bacterial resistance. They can be designed and modified to possess several druggable properties. We report herein a novel hybrid peptide of modified aurein (A3) and cathelicidin (P7), or A3P7, by a flipping technique. It exhibited potent antibacterial activity against both Gram-negative and -positive pathogenic bacteria but had moderate hemolytic activity. To reduce the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…However, none of the D-AAs were able to protect against infection in vitro or in a murine model in vivo, and D-AAs may not be suitable antivirulence agents. A recent study by Jariyarattanarach et al 280 reported the creation of a novel hybrid D-AA of modified aurein and cathelicidin, where the structures were substituted with hydrophobic and positively charged Trp and Arg. The hybrid D-AA exhibited potent antibacterial activity against A. baumannii and killing via membrane disruption and leakage of intracellular contents with a low tendency to induce bacterial resistance.…”
Section: Gram-negative Organisms In Pji and The Effect Of D-aasmentioning
confidence: 99%
“…However, none of the D-AAs were able to protect against infection in vitro or in a murine model in vivo, and D-AAs may not be suitable antivirulence agents. A recent study by Jariyarattanarach et al 280 reported the creation of a novel hybrid D-AA of modified aurein and cathelicidin, where the structures were substituted with hydrophobic and positively charged Trp and Arg. The hybrid D-AA exhibited potent antibacterial activity against A. baumannii and killing via membrane disruption and leakage of intracellular contents with a low tendency to induce bacterial resistance.…”
Section: Gram-negative Organisms In Pji and The Effect Of D-aasmentioning
confidence: 99%
“…The final peptide rapidly killed A. baumannii ATCC 19606 (MIC = 7.81 µg/mL) via membrane disruption and showed a low tendency to induce bacterial resistance. It also exhibited potent antibacterial activity against MDR and XDR A. baumannii (MIC = 3.91–15.63) [ 176 ]. BP214 is a cationic amphipathic all-D decapeptide developed from a short cecropin A-melittin hybrid peptide BP100 [ 300 ], which showed excellent activity against colistin-resistant A. baumannii and modest hemolytic properties [ 301 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…32 Additionally, D-amino acids containing peptide sequences improve therapeutic effects, antimicrobial activity, and enzymatic stability. 33,34 In 1993, Ghadiri et al described hollow peptide nanotubes using alternating D/L-amino acids. 35 Lorenzi and co-workers showed the crystal structures of dipeptides containing alternating D/L-and L/D-amino acids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The inclusion of d -amino acids into peptide sequences offers extensive application in peptide chemistry, medicinal chemistry, biological chemistry, and nanotechnology . Additionally, d -amino acids containing peptide sequences improve therapeutic effects, antimicrobial activity, and enzymatic stability. , In 1993, Ghadiri et al described hollow peptide nanotubes using alternating d / l -amino acids . Lorenzi and co-workers showed the crystal structures of dipeptides containing alternating d / l- and l / d- amino acids .…”
Section: Introductionmentioning
confidence: 99%